HUBUNGAN IKLIM KERJA FISIK DENGAN KELELAHAN SUBYEKTIF DI PABRIK TAHU CV. BUDI SARI JAYA SIDOARJO - Dica Ayu Oktavia; Endang Dwiyanti (Poltekkes Kemenkes Surabaya, 2016)
Tofu factory CV. Budi Sari Jaya is one factory that has physical work climate that is heat because in theproduction process need high temperatures might cause subjective fatigue to workers. The purpose of this studywas to determine the relationship beetwen physical work climate with subjective fatigue in the tofu factory CV.Budi Sari Jaya Sidoarjo. This study was an observational study with cross sectional approach. The sample fromthis study used total population method caused the sample was consisted of 13 people. The results is there aretwo workspace boiler operator area and tofu cooking area that physical work climate exceed the Threshold LevelValue Keywords: physical work climate, subjective fatigue